Numerical Investigation of Terrain-Induced Turbulence in Complex Terrain Using High-Resolution Elevation Data and Surface Roughness Data Constructed with a Drone - Takanori Uchida (Energies, 2019)
Using the method based on unmanned aerial vehicle (UAV) imagery, two kinds of data can be obtained: the digital elevation model (DEM) for the digital expression of terrain, and the digital surface model (DSM) for the digital expression of the surface of the ground, including trees. In this research, a 3D topography model with a horizontal spatial resolution of 1 m was reproduced using DEM. In addition, using the differences between the DEM and DSM data, we were able to obtain further detailed information, such as the heights of trees covering the surface of the ground and their spatial distribution. Therefore, the surface roughness model and the UAV imagery data were directly linked. Based on the above data as input data, a high-resolution 3D numerical flow simulation was conducted. By using the numerical results obtained, we discussed the effect of the existence of surface roughness on the wind speed at the height of the hub of the wind turbine. We also discussed the effect of the differences in the spatial resolution in the horizontal direction of the computational grid on the reproductive precision of terrain-induced turbulence. As a result, the existence and the vortex structure of terrain-induced turbulence occurring near the target wind turbine was clearly revealed. It was shown that a horizontal grid resolution of about 5 m was required to reproduce terrain-induced turbulence formed from topography with an altitude of about 127 m. By the simulation using the surface roughness model, turbulence intensity higher than class A in the International Electrotechnical Commission (IEC) turbulence category was confirmed at the present study site, as well as the measured data.